Berardinelli syndrome. A case report with fatal outcome. - Daher, Elizabeth; Silva Júnior, Geraldo; Benevides, Verônica; Mendon í§a, Patrícia; Bezerra, Helder; Silva, Antônio; Fernandes, Virgínia; Montenegro Júnior, Renan; Fátima Azevedo, María de (Investigación Clínica, 2009)
The aim of this paper is to present the main clinical findings and evolution of a fatal case of Berardinelli Syndrome (congenital generalized lipodystrophy). A 15-year-old girl, followed since the age of three months in the Genetic outpatients”™ clinic, developed insulin resistance when she was eight years old. She had hyperchloremic metabolic acidosis, bilateral retinopathy, proteinuria and hydronephrosis. She was hospitalized several times due to urinary infections. In her last admission she had fever, abdominal pain and was diagnosed urinary sepsis. She presented hemodynamic instability and died, despite all therapeutic measures adopted. Considering the rarity of this syndrome it is important to describe the clinical pre sentation and evolution of this patient with Berardinelli Syndrome, which developed renal dys function and had a fatal outcome.